Find the value of the other unknown by substituting the value of the first
unknown into one of the original equations.
Check the solution by substituting the values of the two unknowns into the
other original equation.
Solve the following system of equations using addition or subtraction.
5x + 6y = 12
3x + 5y = 3
Make the coefficients of y equal in both equations by multiplying the first
equation by 5 and the second equation by 6.
5(5x + 6y = 12) yields 25x + 30y = 60
6(3x + 5y = 3) yields 18x + 30y = 18
Subtract the second equation from the first.
Solve the resulting equation.